Bank efficiency differences across Central and Eastern Europe - Barnabás Székely (Magyar Nemzeti Bank, 2018)
The study evaluates bank efficiency in the EU member states of Central and Eastern Europe (CEE) using stochastic frontier analysis (SFA). Relying on a comprehensive dataset covering the post-crisis period from 2010 to 2016, country-specific average profit and cost efficiencies are calculated. Compared with similar pre-crisis studies, the results highlight the reshuffling effects of the financial crisis. Hungary, for instance, that was consistently found to have a comparatively efficient banking system, now performs well below average. Contrasting the results of traditional performance indicators with SFA supports the mechanism put forward by the Quiet Life Hypothesis. The positive relationship of market share and return on assets (or equity) indicates that higher market power enables banks to realize higher profits. SFA, on the other hand, suggests a negative association implying that banks do not tend to fully exploit this potential.
Keywords: G21; P52; C12; 330; Bank Efficiency; Stochastic Frontier Analysis; Central and Eastern Europe